Evolutionary Genomics of Sex-Related Chromosomes at the Base of the Green Lineage. (1st October 2021) - Benites, Luis Felipe; Bucchini, François; Sanchez-Brosseau, Sophie; Grimsley, Nigel; Vandepoele, Klaas; Piganeau, Gwenaël
Abstract: Although sex is now accepted as a ubiquitous and ancestral feature of eukaryotes, direct observation of sex is still lacking in most unicellular eukaryotic lineages. Evidence of sex is frequently indirect and inferred from the identification of genes involved in meiosis from whole genome data and/or the detection of recombination signatures from genetic diversity in natural populations. In haploid unicellular eukaryotes, sex-related chromosomes are named mating-type ( MT s) chromosomes and generally carry large genomic regions where recombination is suppressed. These regions have been characterized in Fungi and Chlorophyta and determine gamete compatibility and fusion. Two candidate MT+ and MT− alleles, spanning 450–650 kb, have recently been described in Ostreococcus tauri, a marine phytoplanktonic alga from the Mamiellophyceae class, an early diverging branch in the green lineage. Here, we investigate the architecture and evolution of these candidate MT+ and MT− alleles. We analyzed the phylogenetic profile and GC content of MT gene families in eight different genomes whose divergence has been previously estimated at up to 640 Myr, and found evidence that the divergence of the two MT alleles predates speciation in the Ostreococcus genus. Phylogenetic profiles of MT trans-specific polymorphisms in gametologs disclosed candidate MTs in two additional species, and possibly a third. These Mamiellales MT candidates are likely to be the oldest mating-type loci described to date, which makes them fascinating models to investigate the evolutionary mechanisms of haploid sex determination in eukaryotes.